Identification of Predicate Crimes Related to Binary Options Affiliates Money Laundering Crime - Shafira, Maya; Wibowo, Dava Prawira; Husin, Budi Rizki; Amrullah, Rinaldy; Tamza, Fristia Berdian (Jurnal Penegakan Hukum dan Keadilan, 2023)
Binary options are increasingly familiar to the public with online promotions on various social media by Indra Kenz. The link between binary options affiliation and money laundering crimes is that the money generated from promoting binary options is illegal because regulations stipulate that binary options are illegal investments. The research aims to identify predicate crimes related to binary options affiliates in action money laundering crimes. The research is normative juridical with a statute approach. The data used were primary, tertiary secondary. At the same time, data processing was obtained through data selection, classification, and systematization. The data processed was analyzed qualitatively, and conclusions were drawn using inductive methods. Based on the research and discussion results, binary options affiliation could be charged with the predicate crime of fraud as stipulated in Article 378 of the Criminal Code and Article 45A Paragraph (1) Juncto. Article 28 Paragraph (1) Law Number 19 of 2016 concerning ITE. Likewise, with gambling Article 303 Paragraph (1) of the Criminal Code. The results of playing binary options include criminal acts of money laundering due to gambling and fraud, so the origin of money or assets must be hidden first to look legal. The authors suggest that more detailed arrangements are needed to ensnare binary options affiliates. The arrangements can be learned from the modus operandi and approaches regarding affiliates and binary options.